(untitled) (Research, Society and Development, 2019)
The present study aims to present the results of urinary screening performed in the Association of Parents and Friends of Exceptional (APAE) of Itabira in an attempt to identify some Metabolism Inborn Errors. Urine samples were collected from students enrolled in APAE / Itabira without a closed diagnosis in medical records. Eight qualitative urine tests were performed to screen for Metabolism Inborn Errors. Those responsible for the students were informed about the research objectives and only the samples of patients who had signed a Free and Informed Consent Form were collected. Samples of 38 students were analyzed, being 29 male and 9 female. In urine screening, 5 positive results were found for Benedict, 4 doubtful and 1 positive for cetyltrimethylammonium bromide (CTMA), 8 doubtful and 4 positive for Ferric Chloride, 2 doubtful for Dinitrophenylhydrazine, and 3 doubtful for Nitrosonaftol. In order to have a reliable definitive diagnosis, it is necessary to correlate the symptomatology presented by the student and the results obtained, sending the analyzed sample to laboratories that perform specific tests to confirm or cancel the diagnostic hypothesis. The frequency of altered samples demonstrates that urinary screening is a method of easy achievement, low cost and high reliability.